Changes of androgen and corticosterone metabolites excretion and conversion in cystic fibrosis - Podgórski, Rafał; Sumińska, Marta; Rachel, Marta; Pikuła, Barbara; Fichna, Piotr; Bidlingmaier, Martin; Fichna, Marta (Frontiers in Endocrinology, 2023)
Cystic fibrosis (CF) is a life-threatening inherited disease related to a mutation in the CFTR gene, that leads to serious health complications such as chronic pulmonary infections, pancreatic insufficiency, dysfunction of the sweat glands and reproductive system. For the first time, we have described the profile of corticosterone and androgen metabolites in urine, as well as the activity of enzymes involved in steroid genesis and metabolism in people with CF, using gas chromatography/mass spectrometry. A significant reduction in the excretion of most of the measured metabolites in CF was found. These differences were observed in the group of progestagen metabolites, as well as among metabolites of corticosterone and androgens. We revealed higher activities of 17β-hydroxysteroid dehydrogenase and 17,20-lyase in the Δ4 pathway compared with controls, what can promote the androgen synthesis through the backdoor androgen pathway. We have also found the increased conversion activity of 11-oxyganated steroids by 5a-reductase in backdoor pathway. Levels of the most potent and vital androgens (testosterone and dihydrotestosterone) are comparable in both groups. However, the excretion of dehydroepiandrosterone was lower in CF. Decreased cholesterol lipoprotein levels may contribute to limited intracellular cholesterol supply and reduced adrenal steroidogenesis in CF individuals. Changes in the activity of some steroidogenesis enzymes may suggest the presence of some peripheral adaptive mechanisms in CF to maintain androgen balance in the body despite the limited sufficiency of secretion by the adrenal cortex.